2022
DOI: 10.24815/jds.v5i1.20011
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity Biofilm formation of Enterococcus faecalis

Abstract: Biofilm formation is closely related to the pathogenicity of E. faecalis in persistent root canal infections. Limited information is available about the ability and characteristics of E. faecalis biofilm-forming in the persistent pathogenicity of root canal infections. Based on these problems, the purpose of this paper is to improve the molecular understanding of E. faecalis on virulence factors associated with biofilm formation against persistent root canal infections to support laboratory diagnosis and thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…E. faecalis induced an NF-B inflammatory response and impaired DNA damage response and cell cycle control gene expression (Strickertsson et al, 2013). This bacterium has cytolysin and hyaluronidase, which could facilitate migration and collagen fragmentation related to inflammation in host cells (Asmah, 2020). The previous study revealed that the infection of the macrophage precursors by E. faecalis could restrict the plasticity of macrophage change into M2 macrophages (Elashiry et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…E. faecalis induced an NF-B inflammatory response and impaired DNA damage response and cell cycle control gene expression (Strickertsson et al, 2013). This bacterium has cytolysin and hyaluronidase, which could facilitate migration and collagen fragmentation related to inflammation in host cells (Asmah, 2020). The previous study revealed that the infection of the macrophage precursors by E. faecalis could restrict the plasticity of macrophage change into M2 macrophages (Elashiry et al, 2021).…”
Section: Discussionmentioning
confidence: 99%